QUALITATIVE STUDY OF FRAUD IN HEALTH SERVICES AND LEGAL FRAMEWORK IN INDONESIA: A LITERATURE REVIEW - Diaz Alifarizki Zuvarcan; Wardah Yuspin; Arief Budiono (Fakultas Hukum, Universitas Diponegoro, 2025)
Health sector fraud is a significant global challenge that undermines health systems by exploiting financial gains through methods like upcoding and false insurance claims. Despite legal updates, healthcare fraud remains a persistent issue. This study systematically examines fraud detection techniques and the legal framework, providing insights to guide policymakers in developing effective prevention strategies in Indonesia. This research employs a doctrinal research methodology with a literature review approach. Using secondary data from Scopus, PubMed, ScienceDirect, and Google Scholar, this study investigates the patterns, causes, and effects of fraud in the Indonesian healthcare system. This paper reviews nine selected articles and compares them with updated Indonesian legal instruments, mainly Law No. 17 of 2023 on Healthcare and Law No. 1 of 2023 on Criminal Code. The findings demonstrate that although legislative reforms have introduced stricter provisions, their implementation remains inconsistent due to lack of oversight and technology. This study proposes integrative strategies, such as digital audit systems, strengthening legislation, and public reporting mechanisms, to improve fraud prevention. It contributes to the debate by identifying gaps in enforcement and proposing regulatory and technological solutions to strengthen the transparency and integrity of the Indonesian healthcare system.